Geospatial Exposure to Point-of-Sale Tobacco: Real-Time Craving and Smoking Cessation Outcomes - Kirchner, Thomas R. (2013)
BACKGROUND: Little is known about the factors that drive the association between point-of-sale marketing and behavior, because methods that directly link individual-level use outcomes to real-world point-of-sale exposure are only now beginning to be developed. PURPOSE: Daily outcomes during smoking cessation were examined as a function of both real-time geospatial exposure to point-of-sale tobacco (POST) and subjective craving to smoke. METHODS: Continuous individual geospatial location data collected over the first month of a smoking cessation attempt (N=475) in 2010–2012 were overlaid on a POST outlet geodatabase (N=1060). Participants’ mobility data were used to quantify the number of times they came into contact with a POST outlet. Participants recorded real-time craving levels and smoking status via ecologic momentary assessment (EMA) on cellular telephones. RESULTS: The final data set spanned a total of 12,871 days of EMA and geospatial tracking. Lapsing was significantly more likely on days with any POST contact (OR=1.19 [95% CI=1.18, 1.20]), and increasingly likely as the number of daily POST contacts increased (OR=1.07 [95% CI=1.06, 1.08]). Overall, daily POST exposure was significantly associated with lapsing when craving was low (OR=1.22 [95% CI=1.20, 1.23]); high levels of craving were more directly associated with lapse outcomes. CONCLUSIONS: These data shed light on the way mobility patterns drive a dynamic interaction between individuals and the POST environment, demonstrating that quantification of individuals’ exposure to POST marketing can be used to identify previously unrecognized patterns of association among individual mobility, the built environment, and behavioral outcomes.